2021
DOI: 10.1002/nop2.1032
|View full text |Cite
|
Sign up to set email alerts
|

Work community factors, occupational well‐being and work ability in home care: A structural equation modelling

Abstract: The social benefits of occupational well-being and work ability have been rightly demonstrated, as they play a key role in organizational performance, sick leave rates, customer satisfaction, lower employee turnover and intention to retire (Ilmarinen et al., 2008;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Indicators of psychological well-being were viewed as positive self-esteem, rewards, achievements, and sense of belonging as factors related to nurses' positive experiences [33,34]. Indicators of independent competence were work independence, scope of work, and growth experience as factors related to nurses' capability to do the work given to them during their shifts [35,36]. Indicators of social relationships included interpersonal relationships, social advocacy, true collaboration, and authentic leadership as factors related to the network of social relationships with coworkers [37,38].…”
Section: -1 Development Stage (1) Determine Conceptual Frameworkmentioning
confidence: 99%
“…Indicators of psychological well-being were viewed as positive self-esteem, rewards, achievements, and sense of belonging as factors related to nurses' positive experiences [33,34]. Indicators of independent competence were work independence, scope of work, and growth experience as factors related to nurses' capability to do the work given to them during their shifts [35,36]. Indicators of social relationships included interpersonal relationships, social advocacy, true collaboration, and authentic leadership as factors related to the network of social relationships with coworkers [37,38].…”
Section: -1 Development Stage (1) Determine Conceptual Frameworkmentioning
confidence: 99%
“…The International Labour Organization [ 20 ] considers occupational wellbeing as being constructed from all aspects of working life, including the workers’ perceptions of their work, the physical and mental working environment and the working community; considering these aspects will generate healthy, satisfied and engaged workers. The wellbeing was much studied in occupations such as physicians [ 19 ], nurses [ 18 ] and educators [ 21 ], and studies have shown that occupational wellbeing was influenced by leadership style, work environments, social support, employees' opportunities and work relationships [ 18 , 22 , 23 ]. Previous studies have mostly focused on the impacts of work-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Educators' occupational well‐being is related to students' welfare (Harding et al, 2019 ; Saaranen et al, 2015 ), the quality of teaching (Saaranen et al, 2015 ), work productivity (Alker et al, 2015 ) and job retention (Chambers Mack et al, 2019 ; Yedidia et al, 2014 ). A well‐functioning work community with good information policies and work organization (Vauhkonen et al, 2021 ), a positive work atmosphere and employee appreciation (Laine et al, 2018b ) support employee's occupational well‐being. Occupational well‐being, especially about the work community perspective, remains understudied in social and health care education.…”
Section: Introductionmentioning
confidence: 99%